Prolyl-4-hydroxylases 2 and 3 control erythropoietin production in renin-expressing cells of mouse kidneys - Broeker, Katharina A. E.; Fuchs, Michaela A. A.; Schrankl, Julia; Lehrmann, Claudia; Schley, Gunnar; Todorov, Vladimir T.; Hugo, Christian; Wagner, Charlotte; Kurtz, Armin (The Journal of Physiology, 2021)
Activation of the hypoxia-signalling pathway induced by deletion of the ubiquitin-ligase von Hippel-Lindau protein causes an endocrine shift of renin-producing cells to erythropoietin (EPO)-expressing cells. However, the underlying mechanisms have not yet been investigated. Since oxygen-regulated stability of hypoxia-inducible transcription factors relevant for EPO expression is dependent on the activity of prolyl-4-hydroxylases (PHD) 2 and 3, this study aimed to determine the relevance of different PHD isoforms for the EPO expression in renin-producing cells in vivo. For this purpose, mice with inducible renin cell-specific deletions of different PHD isoforms were analysed. Our study shows that there are two subgroups of renal renin-expressing cells, juxtaglomerular renin(+) cells and platelet-derived growth factor receptor-beta(+) interstitial renin(+) cells. These interstitial renin(+) cells belong to the cell pool of native EPO-producing cells and are able to express EPO and renin in parallel. In contrast, co-deletion of PHD2 and PHD3, but not PHD2 deletion alone, induces EPO expression in juxtaglomerular and hyperplastic renin(+) cells and downregulates renin expression. A strong basal PHD3 expression in juxtaglomerular renin(+) cells seems to prevent the hypoxia-inducible transcription factor-2-dependent phenotype shift into EPO cells. In summary, PHDs seem important for the stabilization of the juxtaglomerular renin cell phenotype. Moreover, these findings reveal tubulointerstitial cells as a novel site of renal renin expression and suggest a high endocrine plasticity of these cells. Our data concerning the distinct expression patterns and functions of PHD2 and PHD3 provide new insights into the regulation of renin-producing cells and highlight the need for selective PHD inhibitors. Key points Renal renin-expressing cells can be clearly distinguished into two subgroups, the typical juxtaglomerular renin-producing cells and interstitial renin(+) cells. Interstitial renin(+) cells belong to the cell pool of native erythropoietin (EPO)-producing cells, show a fast EPO response to acute hypoxia-inducible factor-2 (HIF-2) stabilization and are able to express EPO and renin in parallel. Only co-deletion of the prolyl-4-hydroxylases (PHD) 2 and 3, but not PHD2 deletion alone, induces EPO expression in juxtaglomerular renin(+) cells. Chronic HIF-2 stabilization in juxtaglomerular renin-expressing cells leads to their phenotypic shift into EPO-producing cells. A strong basal PHD3 expression in juxtaglomerular renin(+) cells seems to prevent a HIF-2-dependent phenotype shift into EPO cells suggesting PHD3 fulfils a stabilizer function for the juxtaglomerular renin cell phenotype.
CRIS-Team WoS Importer:2022-01-07